Investigation of Petrological Characteristics of The Upper Mantle in Hadji-Abad Ophiolitic Complex (South of Iran): Based on Mineral Chemistry - Mojtaba SoltaniNezhad; Hamid Ahmadipour; Abbas Moradian; Azam Zahedi; Kazuo Nakashima (Journal of Sciences, Islamic Republic of Iran)
The mantle peridotites of the Hadji-Abad ultramafic complex in Hormozgan province, show some petrological evolutions of the upper mantle of southern Iran. The complex includes harzburgite, lherzolite, dunite and chromitite. Evidences such as different generations of minerals, lobate boundaries between grains, elongation of cr-spinels and pyroxenes, incongruent melting related textures and exsolution lamellae of clinopyroxene in orthopyroxene show that the rocks in this peridotites have past a complex petrological history. The chemical composition of chromites in the Hadji Abad dunites and chromitites is similar to that of boninite melts, while, the mineral chemistry of the harzburgitic and lherzolitic show that the host peridotites belong to the upper mantle and have been depleted from incompatible elements due to 15 to 20 percent partial melting. Geo-thermometric calculations reveal that the studied peridotites equilibriated in upper mantle and spinel-peridotite stability field. Using tectonomagmatic discrimination diagrams shows that the Hadji-Abad ultramafic complex is part of an oceanic lithosphere above suprasubduction zone which has undegone partial melting, high temperature deformations and mantle metasomatism processes associated with this environment. These evidences along with the geological and tectonic setting of the Hadji Abad complex adjacent to the Zagros thrust indicate that the complex probably was created in a suprasubduction zone oceanic mantle section and then tectonically emplaced as part of Esfandagheh-Hadji-Abad mélange in the current situation during the upper Cretaceous. This information confirm the dependence of the Esfandagheh-Hadji-Abad ophiolite mélange on the Neotethyan oceanic lithosphere in southern Iran.